Systematic assessment of multi‐echo dynamic susceptibility contrast MRI using a digital reference object. Issue 1 (9th August 2019) - Stokes, Ashley M.; Semmineh, Natenael B.; Nespodzany, Ashley; Bell, Laura C.; Quarles, C. Chad
Abstract : Purpose: Brain tumor dynamic susceptibility contrast (DSC) MRI is adversely impacted by T1 and T 2 ∗ contrast agent leakage effects that result in inaccurate hemodynamic metrics. While multi‐echo acquisitions remove T1 leakage effects, there is no consensus on the optimal set of acquisition parameters. Using a computational approach, we systematically evaluated a wide range of acquisition strategies to determine the optimal multi‐echo DSC‐MRI perfusion protocol. Methods: Using a population‐based DSC‐MRI digital reference object (DRO), we assessed the influence of preload dosing (no preload and full dose preload), field strength (1.5 and 3T), pulse sequence parameters (echo time, repetition time, and flip angle), and leakage correction on relative cerebral blood volume (rCBV) and flow (rCBF) accuracy. We also compared multi‐echo DSC‐MRI protocols with standard single‐echo protocols. Results: Multi‐echo DSC‐MRI is highly consistent across all protocols, and multi‐echo rCBV (with or without use of a preload dose) had higher accuracy than single‐echo rCBV. Regression analysis showed that choice of repetition time and flip angle had minimal impact on multi‐echo rCBV and rCBV, indicating the potential for significant flexibility in acquisition parameters. The echo time combination had minimal impact on rCBV, though longer echo times should be avoided, particularly at higher field strengths. Leakage correction improved rCBV accuracy in all cases. Multi‐echo rCBF was less biased than single‐echo rCBF, although rCBF accuracy was reduced overall relative to rCBV. Conclusions: Multi‐echo acquisitions were more robust than single‐echo, essentially decoupling both repetition time and flip angle from rCBV accuracy. Multi‐echo acquisitions obviate the need for preload dosing, although leakage correction to remove residual T 2 ∗ leakage effects remains compulsory for high rCBV accuracy.